GROWTH AND NUTRITIONAL EFFICIENCY OF NITROGEN IN CULTIVARS OF FORAGE MILLET IN THE AMAZON - Melo, Nilvan Carvalho [UNESP]; Fernandes, Antonio Rodrigues; Galvao, Jessivaldo Rodrigues (Univ Fed Rural Semi-arido-ufersa, 2015)
The millet is a forage with high yield potential, mainly due to its high tolerance to water deficit and adaptation to soils of low fertility. Even being adapted to soils of low fertility, it is responsive to nitrogen fertilization. The objective was to evaluate the growth and nutritional efficiency of millet forage cultivars, due to nitrogen (N). The experiment was carried out in a greenhouse, in a typical Yellow Oxisol Dystrophic. The experimental design was a completely randomized design, arranged in a 4 x 2 factorial scheme with six repetitions. The factors were the control treatment (without fertilization with N) and three doses of N (75, 150 and 225 kg ha(-1)) in the form of urea and ammonium sulfate and two cultivars of pearl millet (BN2 and ADR500). The harvest was performed 80 days after the emergency. The higher production of dry matter of aerial part was obtained with the estimated dose of 179 kg ha(-1) of N. The cultivar ADR500 showed the highest height and greater efficiency of translocation, while the BN2 showed higher N content of the aerial part and roots. The greater efficiency of use and translocation of N were achieved with doses estimated for 109 and 133 ha(-1) of N for the cultivars ADR500 and BN2, respectively.
Keywords: Dry matter; Nitrogen fertilization; Use Efficiency